PTU-060 Management of pouch strictures in restorative proctocolectomy. a tertiary centre experience with a treatment algorithm. (8th June 2018) - Segal, Jonathan; Penez, Lawrence; Tozer, Phillip; Allison, Lisa; Faiz, Omar; Clark, Susan; Hart, Ailsa
Abstract : Introduction: Restorative proctocolectomy (RPC) with ileal pouch-anal anastomosis (IPAA) removes the diseased colon and rectum, for example in ulcerative colitis, and preserves gastrointestinal continuity, meaning a permanent stoma can be avoided. Pouch strictures have a reported incidence of 5%–38%. The two common stricture locations are the pouch-anal anastomosis and the pouch inlet. The reported incidence of pouch-anal anastomotic strictures ranges from 7.8% to 14% with a prevalence as high as 38%. Strictures also develop in the mid-pouch. Mid-pouch strictures are less well understood in terms of aetiology, incidence, management and outcomes. They are of particular interest from a surgical perspective as they are hard to access at EUA and therefore alternative management options need to be explored. The management of pouch strictures include medical options, such as immunosuppressant and biological therapy, endoscopic management with balloon dilatation, or surgical management including, Hegar dilatation, stricturoplasty, pouch revision, diversion or pouch excision. There are limited data on the success of these techniques. Methods: Patients were identified between January 2008 to January 2017. Patients were identified from the endoscopy, biologics and pouch databases at our institution. Review of the clinical records was used to determine those who had pouch strictures. The primary outcome measure was avoidance of pouch failure. Pouch failure was defined as the need for defunctioning or pouch removal at last follow-up. Results: Forty-nine patients with pouch strictures were included in the study. Initial therapy for the treatment of pouch strictures was associated with pouch retention in a quarter of those treated with biological therapy, 87% for Hegar dilatations and 80% for balloon dilatation with median follow-ups of 31 months, 16 months and 12 months respectively. Conclusion: Hegar dilatation should be considered the initial management approach for pouch-anal anastomotic strictures. Endoscopic balloon dilatation should be considered as first line therapy for both mid-pouch and inlet strictures. Limited evidence suggests that inflammatory inlet strictures are likely to be the most responsive to biological therapy.